AMOR COM HUMOR: A RECRIAÇÃO DO EPITALÂMIO NA POESIA DE JOSÉ PAULO PAES - Renan Pires Cornette (Linguagem: Estudos e Pesquisas, 2013)
One of the characteristics of the poetry of José Paulo Paes is the recuperation of classical traditional forms adjusting the models of the past to his personal diction by using critical dislocation. This occurs with the epithalamium, a lyrical composition that was originally practiced by the Greeks in honor of newlyweds. Amongst the Romans it took on a pornographic character and was ratified traditionally by self-seeking flattery. This article proposes to analyze three epithalamiums written by the poet, seeking to show the traces of difference inserted by the poet in this classical lyric form.